2011
DOI: 10.2139/ssrn.2004361
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Students' Evaluations of Professors

Abstract: This paper contrasts measures of teacher effectiveness with the students' evaluations for the same teachers using administrative data from Bocconi University. The effectiveness measures are estimated by comparing the performance in follow-on coursework of students who are randomly assigned to teachers. We find that teacher quality matters substantially and that our measure of effectiveness is negatively correlated with the students' evaluations of professors. A simple theory rationalizes this result under the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 150 publications
7
43
1
1
Order By: Relevance
“…Effectiveness in teaching large introductory courses could be measured by assessing how well students perform later in more advanced courses. One recent study examined such a setting, in which economics students at Bocconi University were randomly assigned in introductory economics courses (Braga, Paccagnella, and Pellizzari 2014 ). The authors found that, indeed, SETs are significantly correlated with success in more advanced courses-but in the wrong direction .…”
Section: Resultsmentioning
confidence: 99%
“…Effectiveness in teaching large introductory courses could be measured by assessing how well students perform later in more advanced courses. One recent study examined such a setting, in which economics students at Bocconi University were randomly assigned in introductory economics courses (Braga, Paccagnella, and Pellizzari 2014 ). The authors found that, indeed, SETs are significantly correlated with success in more advanced courses-but in the wrong direction .…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, some research shows a positive link between teaching effectiveness and student evaluations (Beleche, Fairris, and Marks, 2012). However, this link is often weak and other research has shown that effectiveness as measured by performance in follow-on courses is insignificantly or negatively correlated with teaching evaluations (Weinberg, Hashimoto, and Fleisher, 2009;Carrel and West, 2010;and Braga, Paccagnella, and Pellizzari, 2014). Student composition and class setting may also explain the positive correlation if preexisting student or class characteristics are associated with both earning higher grades and giving better evaluations.…”
Section: Institutional Details and Datamentioning
confidence: 99%
“…This is a valid instrument if core and graduate classes do not impact evaluations aside from the impact they have on grades. Other papers suggest that grades impact evaluations by testing implications of the various hypotheses (Greenwald and Gilmore, 1997) or showing that there is not a link between grades and learning (Braga, Paccagnella, and Pellizzari, 2014). 6 Regional campuses account for another 14,000 enrollments, but this analysis only covers the main campus.…”
Section: Institutional Details and Datamentioning
confidence: 99%
“…2 Braga et al (2014) show that students' evaluations of teachers are negatively correlated with a more objective measure of teaching effectiveness and quality, which is student performance in subsequent coursework. Becker and Watts (1999) assess data from a survey among economics departments in the US and show that student evaluations of teaching explain less than 50 percent of the variation in student learning outcomes.…”
Section: Introductionmentioning
confidence: 99%